Highly efficient scavenging of nitrophenol, arsenic (V), copper (II), dibenzothiphene, and carbazole by nanoporous silica/carbon adsorbents for remediation of oil and water pollutants - Ghasem Zolfaghari (Journal of Water and Environmental Nanotechnology)
At present study, the removal of p-nitrophenol (PNP) by a newly designed mesoporous organocarbon, monolayers of ß-cyclodextrine (CD) on oxidzed ordered nanoporous carbon (OX-ONC) via 1,4-phenylene diisocyanate (PDI) linking denoted as CD-ONC was optimized. Furthermore, Au-doped mesoporous carbon CMK-3 denoted as Au-OCMK-3 was synthesized by using SBA-15. Au-OCMK-3 has been studied for removal of dibenzothiphene (DBT) and carbazole (CA) from n-hexane. Also the functionalization of SBA-16 mesoporous with sulfonic acid for arsenic (As (V)) and copper (Cu (II)) removal were carried out (SBA-16-SO3H). Maximum absorption capacity of CD-ONC was 100 mg/g. Dubinin–Radushkevich isotherm was applied to describe the nature of PNP uptake and it was found that it occurred physically (E = 0.07 KJ/mol, CD-ONC). Value for Temkin’s heat of adsorption is positive for PNP (157.87 J/mol, CD-ONC). There are two physisorption models of PNP with the surface C=O groups of ONC (H-bond and dispersion effect between phenolic ring and π electrons). The overall PNP adsorption process was exothermic and spontaneous in nature according to thermodynamics parameters (free energy (ΔGo), enthalpy (ΔHo), and entropy (ΔSo)). We demonstrate that functionalization of CMK-3 with gold is possible (qm value for DBT: 15.33 mg/g and for CA: 13.00 mg/g). The adsorption capacity for As (V) on SBA-16- SO3H reaches 92.63 mg/g. The high removal of As equilibrium time of 90 minutes can be explained in terms of a strong electrostatic attraction that occurred between the SO3H and As. Maximum absorption capacity was 92.63 mg/g for As(V) was and 13.00 mg/g for Cu(II).